Tata Kelola Transportasi Berkelanjutan di Kota Surabaya : Studi pada Suroboyo Bus Listrik - Hermayandi, Nandina Salsabila; Pradana, Galih Wahyu (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
As a metropolitan city, Surabaya has to deal with greenhouse gas emissions that come from the transportation sector, which is about 52% of the total. So, the Suroboyo Electric Bus is supposed to be an eco-friendly solution. But, there are still some issues, like not enough bus stops, charging takes a long time, and indirect emissions from the power source. This study employs a qualitative descriptive method to analyze sustainable transportation governance based on ten principles according to Tamin (2007). The results indicate that most principles have been implemented, though not optimally. Regarding the principles of accessibility and social justice, bus stops are still unsafe, and seat classifications are not used as intended. The principles of environment, health, and safety are reflected in reduced air pollution and greenhouse gas emissions, but seatbelt usage remains low. Public participation is quite active, but information transparency has not reached all segments of society. The economic principle is reflected in affordable fares and energy cost efficiency, but ticket integration is not yet comprehensive. The information and analysis principle shows openness to aspirations, but there has been no follow-up publication, including on NGO advocacy. Capacity building has been conducted for staff, but public education remains limited. A network among stakeholders has been established, but coordination regarding departure schedule and charging remains a challenge. Therefore, a comprehensive evaluation is needed to support the realization of an inclusive, efficient, and sustainable transportation system.